Agreeing a set of biopsychosocial variables for collection across the UK Eating Disorders Clinical Research Network: a consensus study using adapted nominal group technique - Lu Qi; Sarah Byford; Agnes Ayton; Sabine Landau; Gerome Breen; Dasha Nicholls; Ulrike Schmidt; Daniel Munblit; Tom Jewell; James Downs; Stephen Anderson; Anna Carnegie; et al. (BMJ Mental Health)
Background Eating disorders are serious psychiatric disorders associated with high levels of co-occurring physical and mental health conditions and poor treatment outcomes. The collection of standardised, routinely collected data within clinical services holds promise to improve patient care.Objective To agree on a set of biopsychosocial variables for routine data collection within eating disorder services in the UK.Methods Two online workshops were conducted using an adapted nominal group technique to agree on priorities for data collection in adult and child/adolescent eating disorder services. Workshop participants (n=43) consisted of people with lived experience, carers, clinicians and researchers. Two researchers independently conducted a reflexive thematic analysis of the workshop transcripts to identify qualitative priorities for data collection. Descriptive statistics were used to analyse the results of online voting.Findings Thematic analysis identified four superordinate themes for data collection in eating disorder services: (1) a mutually valued and beneficial collaboration; (2) a holistic approach; (3) a balance between standardisation and individualisation; (4) doing no harm. Quantitative analysis of voting identified priorities across a range of domains, leading to a proposed biopsychosocial dataset.Conclusions This project agreed on a set of biopsychosocial variables for routine data collection in the UK Eating Disorders Clinical Research Network. Further research should evaluate the implementation success of these variables.Clinical implications Patients, caregivers and clinicians support routine data collection in eating disorder services so long as the measures used are considered meaningful, not overly burdensome, non-stigmatising and collected in collaboration between patients and treatment providers.